Initial development of the endocarp in Lithraea brasiliensis Marchand (Anacardiaceae): with taxonomic notes - OLIVEIRA,JOÃO M.S. DE (2015)
Investigation into the initial developmental stages of a given structure is fundamental for precise characterization as well as for comparative analysis in relation to other taxa when homologies are established. For the Anacardiaceae family, investigations of the initial development of the pericarp or its basic histological sites, the epicarp, mesocarp and endocarp, are relevant since these regions are of taxonomic and phylogenetic importance. The initial stages of endocarp development in Lithraea brasiliensis were studied using light microscopy. In L. brasiliensis, the fruits are of the drupe type. The endocarp originates exclusively in the epidermis of the locular cavity and is composed of only three strata. The crystalliferous layer, typical in fruits of the Anacardiaceae family, originates in the carpelar mesophyll and runs adjacent to the outermost layer of the endocarp. The endocarp in Lithraea brasiliensis is of the Anacardium type. The results of the present study are important for the identification of theLithraea species that occur in the state of Rio Grande do Sul. In L. molleoides, the crystalliferous layer was shown to originate from the locular epidermis and this developmental aspect enables it to be differentiated from L. brasiliensis and demonstrates that there is variability of endocarp development in Lithraea.